Evaluating the Effects of the COVID-19 Pandemic on Daily Market Return in Pakistan Stock Exchange - Abbas, Musarat; Mansha, Muhammad; Rahman, Saeed ur (iRASD Journal of Economics, 2023)
The capital markets are highly interconnected in the modern economic system, and it is one of the most vulnerable sectors to any financial and natural disaster occurring around the globe. The COVID-19 pandemic not only affects the capital market of the host nation but also creates problems in other parts of the world’s capital markets as well. The main objective of this event study is to empirically analyze the impacts of the COVID-19 pandemic on the daily stock market returns in Pakistan, which is a fast-growing and emerging market in South Asia. For this, we used secondary data to evaluate the effects of COVID-19 in different dimensions i.e., total cases, new cases, total deaths, new deaths, and the positive rate on the daily stock returns of 531 listed companies in the Pakistan stock exchange over the period of March 2020 to November 2021. For stationarity of the variables, we applied an augmented Dickey-Fuller (ADF) unit root test. The results of the study obtained through ARCH family regression estimation revealed that the total number of cases, new cases, and the positive rate are negatively affecting the stock market returns in Pakistan while the total deaths and new deaths are positively affecting the stock market returns during the pandemic.